User Centered Portable Suspension Therapy Unit Design & Testing on Healthy Volunteers - Kaviarasu Mahalingam1, Karthikeyan Jayabalan1, Sree Vamsi1, Yu Chye Wah2, Angeline Qnah Lie Mun3, Kh (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Suspension is a therapeutic skill that suspends a body and eliminates effects of friction to easethe movements. It is very beneficial in both musculoskeletal and neurological field.Objective: To make suspension therapy more accessible for a physiotherapist domestically which providean opportunity for patient to receive suspension therapy in any occasion.Study Design: Pilot study.Sample Size: 30 healthy subjects from Hospital or AIMST University (with various body sizes).Discussion: The overall satisfaction level for the Portable Suspension Kit is pleasant. The subjectsacknowledge that suspension therapy helps to improve range of motion and is suitable for home rehabilitationand both statements score the highest which is 3.9667±0.66868 out of 5. On the contrary, the subjects agreeless on the stability of the frame which results show 3.7±0.98786 out of 5. Whereas, for R.A. tracker, theoutcome of accuracy level turned out to be 65.2% which is of moderate range and the result is acceptable fora new prototype. P > 0.652 is not statistically significant due to the sensor sensitivity of calibration. Thus, westrongly agree that the deficiency needed to be improved to allow accurate visual feedback.Conclusion: The making of ‘Portable Suspension Kit’ is successful and indeed is convenient to carry around.Suspension therapy can now be widely used in any occasion on the patients. Nevertheless, it still has more toimprove especially on the stability and the material used to make it safer, lighter and easier to carry.